2016
DOI: 10.5489/cuaj.3362
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Nephroureterectomy is Associated with Higher Risk of Adverse Events compared to Laparoscopic Radical Nephrectomy

Abstract: Introduction: Laparoscopic radical nephrectomy (LRN) and laparoscopic nephroureterectomy (LNU) are similar procedures and some surgeons may believe the perioperative risks are the same. The purpose of this study is to characterize and compare complications following LRN and LNU. Methods: A historical cohort of patients who received either LRN or LNU between 2006 and 2012 was reviewed from the National Surgical Quality Improvement Program (NSQIP) database. Patient characteristics, surgical characteristics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Previous studies reported a postoperative complication rate of 20.8% and a postoperative mortality rate at 90 days after surgery of 4.4% in similar populations (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a postoperative complication rate of 20.8% and a postoperative mortality rate at 90 days after surgery of 4.4% in similar populations (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Complete retroperitoneal laparoscopic radical resection in all these patients was carrying out [15] proposed a solution: using a linear cutting occluder to perform a sleeve-like resection of the bladder tissue around the ureteral opening. At the same time, the stump was sealed to avoid the urine leakage and prevent the spread of tumor as possible.…”
Section: Resultsmentioning
confidence: 99%
“…21 In severe cases, multiple abscess drainages may be required, which underscores the clinical and economic importance of understanding and mitigating the risk factors for SSIs. 22 Our study analysed data from a cohort of 90 patients who underwent laparoscopic urologic procedures, with 30 cases developing infections postoperatively. The statistical analysis delineated a significant association between several factors and the development of SSIs.…”
Section: Discussionmentioning
confidence: 99%